Performance -Based Budgeting in the Public Financing of the Culture Sector in Poland - Suchecki, Adam Mateusz (Studia Oeconomica Posnaniensia, 2013)
In 2006 the process of implementing performance-based budgeting and NPM methods, which is used in many countries of Western Europe and recommended by, for example, the European Union and OECD, has begun in Poland. Th e main aim of this article is the presentation of these process in Poland in the culture sector and an evaluation of the future effects of implementing changes.